Pitumpanua Community Complaint Service Based on Software Development Life Cycle - Arief, Husniah; Azhari, Ahmad (Signal and Image Processing Letters, 2023)
Public services generally only provide suggestion box to people who have complaints. In the ongoing complaints, namely the people use written media (suggestion and complaint boxes) and oral media (face to face with employees). The complaint handling system is not stored in the database which causes the unknown number of complaints that have or have not handled so that the handling of complaints is delayed or skipped. Every complaint that is recorded manually will attack the search for data and is not efficient because complaints must be met directly and do not rule out data being damaged or lost because there is no backup. This study aims to develop a Community Complaint Application in the Pitumpanua District and to find out the results of testing the Community Complaint Application in the Pitumpanua District. This study uses a model waterfall development with data collection techniques using techniques interviews, and questionnaires to measure the feasibility of the device software that has been developed with several Respondentts. System testing in this study uses several standards the quality of software development, namely ISO 25010, among others are functional suitability with good category results, very good usability, portability with good category results, Based on the results research is produced a Complaint Application Development Website-Based Society that can be used to make public complaints and manage the administration of public complaint reports.